An Examination of Academic-Practitioner Co-Authorship Trends in Supply Chain Management Journals - Shona Morgan; Carin Lightner-Laws (International Journal of Supply Chain Management, 2013)
The purpose of this research is to explore the extent that academics and practitioners collaborate to publish research in academic journals as evidenced by co-authorship. Using journal rankings studies, fourteen top-ranked peer reviewed academic journals that publish supply chain management (SCM) research are identified. Each article within our journal sample is examined over an eleven year period beginning in 2000 for academic-practitioner co-authorship. Results indicate that approximately nine percent of a near census of 5,064 articles are co-authored between academics and practitioners. Finally, practitioner authors are classified into five different groups in order to have a more fine-grain view of the distribution of author-type by journal. Analysis shows that some journals are more inclined to publish certain types of academic-practitioner co-authored articles over others. Implications for future supply chain management research are discussed, advocating for more collaborative research between academics and practitioners within the field.